Perilaku Konsumen Dan Manajemen Strategi Mcdonald's Pasca Pandemi Covid 19 - Sepania Tiarasi Lumban Tobing; Linsa Febby Br Barus; Junedi Sugianto Pakpahan; Lenti Susanna Saragih; Aurora Elise Putriku (Student Scientific Creativity Journal, 2024)
The purpose of writing this article is to analyze McDonald's organizational behavior and strategic management after the covid 19 pandemic. Even though McDonald's has obtained permission from the government, the company still has to make new strategies to make trade tactics in order to maintain consumer loyalty. Of course, the managerial side will determine a series of designs based on elements of organizational behavior to create new innovations in terms of McDonald's products and services in order to be able to improve and adapt again from the pandemic to endemic transition. So that when it enters the new normal era, of course there are still people who are still carried away by the habit of eating Ria from various online applications. Seeing this phenomenon, McDonald's tries to design various strategies through innovation in organizational behavior and management support to adapt back after the pandemic